PROGRAM KEMITRAAN KELOMPOK MASYARAKAT UNTUK MENCEGAH DAN MENGONTROL HIPERTENSI DENGAN EFFLEURAGE BACK MASSAGE DI PUSKESMAS SANANWETAN KOTA BLITAR - Sepdianto, Tri Cahyo; Suprajitno, Suprajitno; Ciptaningtyas, Maria Diah (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Hypertension is a non-communicable disease, with cases continuing to increase every year. Early detection of hypertension and management of hypertension through activity patterns and nutrition, as well as other non-pharmacological management such as effleurage back massage, are very important to control blood pressure in hypertension sufferers. The aim of this social project was to increase cadres' knowledge and skills in preventing and managing hypertension. The method was community empowerment through outreach activities about hypertension, early detection and management of hypertension, and non-pharmacological management training with effleurage back massage to control blood pressure in hypertension sufferers. The activity was attended by 25 POSBINDU PTM cadres in the Sananwetan Community Health Center, Blitar City. The results of the activity showed that there was an increase in cadres' knowledge of preventing and managing hypertension. Cadres' skills in non-pharmacological management through effleurage back massage were also increased. Effleurage Back Massage is a non-pharmacological management that can be easily applied by POSBINDU PTM cadres to hypertensive patients to control blood pressure and prevent complications.